Prenatal dietary exposures and offspring body size from 6 months to 18 years: A systematic review. Issue 2 (3rd February 2020) - Litvak, Jacqueline; Parekh, Niyati; Deierlein, Andrea
Abstract: Background: In utero dietary exposures may influence childhood obesity. Objectives: To evaluate the relationship between prenatal dietary exposures and offspring body size from 6 months to 18 years. Data sources: Articles were identified in PubMed and Web of Science (January 2010‐March 2018) using the PRISMA guidelines. Additional studies were identified through a reference review of articles that met the inclusion criteria and related reviews. Study selection: Prospective cohort studies that assessed dietary patterns, foods, macronutrients, or beverages during healthy pregnancy and offspring body size. The extraction of articles was done using predefined data fields. Synthesis: One author extracted all information and evaluated bias with the NHLBI's Quality Assessment Tool. Results: A total of 851 research articles were evaluated. Twenty‐one studies assessing dietary patterns, macronutrients, foods, and beverages met inclusion criteria. Consumption of a Mediterranean dietary pattern during pregnancy was associated with reduced body size, while refined carbohydrates were associated with offspring obesity. No association was observed between data‐driven dietary patterns and offspring body size, as well as a pro‐inflammatory diet pattern and offspring body size. Mixed and null findings were observed for the relationship between total carbohydrates, n‐3 polyunsaturated fatty acids, protein, sugar‐sweetened beverages, and artificially sweetened beverages and offspring body size. Conclusions: Adhering to a Mediterranean diet and limiting refined carbohydrates during pregnancy may influence offspring body size between 6 months and 18 years. The diverging results that exist between studies highlight the complexity of this topic.